1984
DOI: 10.1159/000173661
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Venous Pulsatility Detected by Doppler Method for Diagnosis of Right Heart Failure

Abstract: This study shows that peripheral venous flow detected by Doppler ultrasound becomes synchronously pulsatile with heart beats as soon as central venous pressure (CVP) is above 7 mm Hg. CVP was above 7 mm Hg in 13 among 46 patients. Clinical signs of right heart failure were detectable in only 7 of these 13 patients (sensitivity 54%), whereas peripheral venous flow was pulsatile in 12 of them (sensitivity 92%). In 4 patients with a normal CVP, peripheral venous flow was also pulsatile; all of them suffered from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 3 publications
2
13
0
Order By: Relevance
“…When the central venous pressure (CVP) is high, the effect of the cardiac pulsations on peripheral veins is significant. 2 In our study, the right atrial pressure, a more objective sign of right-sided cardiac function than clinical findings, was compared to the flow velocities and PIs. Our results showed that an increase in right atrial pressure did not influence antero-grade flow velocities in the peripheral veins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the central venous pressure (CVP) is high, the effect of the cardiac pulsations on peripheral veins is significant. 2 In our study, the right atrial pressure, a more objective sign of right-sided cardiac function than clinical findings, was compared to the flow velocities and PIs. Our results showed that an increase in right atrial pressure did not influence antero-grade flow velocities in the peripheral veins.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with rightsided cardiac dysfunction, the venous flow pattern in the patient's lower extemities tends to be pulsatile. [1][2][3] Abu-Yousef et al 1 found a significant correlation between increased right atrial pressure and pulsatile venous flow in the lower limbs. The visceral venous system also experiences flow variations caused by fluctuating right atrial pressure.…”
Section: Received 16 March 2000; Accepted 25 September 2000mentioning
confidence: 97%
“…A, Normal LLVD sonographic venous tracing shows each waveform is made up of four waves that also span 1.2 s (one cardiac cycle on ECC tracing). Note that the initiation of the systolic wave (5), which begins at the crossing of the tracing with the baseline right after the 11 wave (a) on the Doppler tracing, is delayed by 0.4 s after the QRS complex (star on the ECC tracing). Titis is due to the collapsed state of the JVC Note that this interval was shorter in the TR patient in Figure 5, thought to be due to the speedy transmission that occurs when the IVC is dilated.…”
Section: Discussionmentioning
confidence: 99%
“…3,[16][17][18] Nonetheless, hardly any publications in the medical literature correlate the rise in right atrial pressure with the pulsatile wave spectrum in Doppler studies in the lower limbs. Krahenbuhl and coworkers were the first, in 1984, 4 and they obtained a sensitivity of 92%, a specificity of 89%, a PPV of 75%, and an NPV of 97% using Doppler interrogation. The optimum results of this series could be due to the unrefined measuring method, since it was based on recognizing a sound and did not have a baseline that allowed the researchers to detect retrograde flow objectively.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 We therefore investigated the relationship between high atrium pressure and pulsatile or retrograde flow in the CFV. We based our study on pulsed Doppler sonographic work on the liver that links portal vein pulsatility to congestive failure 6 and other studies that consider the suprahepatic vein pulsatility as a sign of tricuspid regurgitation.…”
mentioning
confidence: 99%